1976
DOI: 10.1002/jbm.820100612
|View full text |Cite
|
Sign up to set email alerts
|

New types of synthetic infusion solutions. III. Elimination and retention of poly‐[N‐(2‐hydroxypropyl)methacrylamide] in a test organism

Abstract: The elimination and retention of a new, fully synthetic plasma prosthesis of Czechoslovak origin under the working name of Duxon (poly[N-(2-hydroxypropyl)methacrylamide]) was investigated in experiments on rabbits by using a 14C-labeled polymer. Results published earlier on elimination have been confirmed and extended. Retention was examined after repeated application. The effect of molecular weight prevailed both in elimination and in retention. Polymers of lower molecular weights, which possess a good therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…HPMA copolymers have been shown in other systems to be nonimmunogenic, biocompatible drug carriers [20,21]. Recent data from phase I clinical trials of HPMA copolymer-doxorubicin conjugates have demonstrated the biocompatibility of the conjugates in humans [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…HPMA copolymers have been shown in other systems to be nonimmunogenic, biocompatible drug carriers [20,21]. Recent data from phase I clinical trials of HPMA copolymer-doxorubicin conjugates have demonstrated the biocompatibility of the conjugates in humans [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Poly-N-(2-hydroxypropyl) methacrylamide, pHPMA, is a neutral and biocompatible polymeric carrier used to prepare different soluble drug conjugates with a high residence time in plasma and low tissue distribution compared to other polymer systems [1][2][3][4][5]. Because of this well-known performance in physiological media, this neutral polymer has been studied for more than a decade as sterical stabilizer of polycation-DNA complexes or polyplexes, in order to modulate their positive charge density and hydrophilia, in an attempt to avoid nonspecific interactions with both the cellular membrane and plasma components.…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxypropylmethacrylamide polymers were originally developed as potential plasma expanders and have a long safety record in man (6,7). The initial studies of the use of hydroxypropylmethacrylamide copolymers as potential delivery systems for Pt-containing drugs were reported by Duncan et al (8) who constructed an hydroxypropylmethacrylamide copolymer to which cisplatin was linked via a tetrapeptide GFLG coupled to an ethylenediamine chelating group.…”
mentioning
confidence: 99%